(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
Incurable diseases represent a significant challenge to modern medicine, encompassing a wide range of conditions that cannot be permanently eliminated with current scientific knowledge and technology. These diseases include neurodegenerative disorders, autoimmune conditions, chronic illnesses, certain genetic disorders, and advanced-stage cancers. Despite the lack of cures, many of these diseases can be managed through medications, therapies, and lifestyle adjustments that improve patient outcomes and quality of life.